2018
DOI: 10.3390/logistics3010002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supply Chain Design and Collaboration on Customers’ Satisfaction of Instant Noodles in Ekiti State, Nigeria

Abstract: The degree of collaboration among supply chain partners and the structure of the network are important determinants of the level of satisfaction customers derive from the products or services. However, the effects of these dimensions on customer satisfaction at the downstream section of the supply chain remain under-researched in Nigeria. This study precisely examined the effects of collaboration and supply chain design on customers’ satisfaction at the downstream end of the chain using Ekiti State as study ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…They represent the efficiency and effectiveness offered to the overall supply chain [17]. Additionally, collaboration in the supply chain can improve performance by minimizing the demand and supply uncertainty, improve revenue, reduce cost, and increase flexibility [31]. Many studies have found that a higher level of supply chain collaboration can improve the firms' performance, especially in logistics activities [32,33].…”
Section: Benefits Of Collaborative Relationshipsmentioning
confidence: 99%
“…They represent the efficiency and effectiveness offered to the overall supply chain [17]. Additionally, collaboration in the supply chain can improve performance by minimizing the demand and supply uncertainty, improve revenue, reduce cost, and increase flexibility [31]. Many studies have found that a higher level of supply chain collaboration can improve the firms' performance, especially in logistics activities [32,33].…”
Section: Benefits Of Collaborative Relationshipsmentioning
confidence: 99%